PENGARUH WORD OF MOUTH PADA MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ONLINE GROCERIES X - Kusumah, Friday Arianty; Kusno, Kuswarini (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Online groceries X does marketing through social media Instagram to reach consumers. However, communication between consumers on Instagram online groceries X Instagram is still low. The study's objectives are 1) to describe the characteristics of consumers who make purchasing decisions at online groceries X and 2) to analyze the influence of word of mouth on Instagram social media on consumer decisions in purchasing products at online groceries X. The study’s design is quantitative with survey techniques. The 70 samples were selected using a simple random sampling technique. Primary data were analyzed using descriptive analysis and multiple linear regression analysis. Based on the results of the study, online groceries X's consumer characteristics are dominated by women, averaged aged 30,4 years with range 34 years, domiciled in DKI Jakarta, have a high-educated, work as a private employee, earn >Rp6,000,000, married, and follow online groceries X's Instagram. Simultaneously, the variables of intensity, the valence of opinion, and content significantly influence purchasing decisions. Partially, the intensity variable has a significant influence on the purchase decision whereas the valence of opinion and content variables do not have a significant influence on the purchase decision. The R2 value shows that the purchase decision variable can be explained by the intensity, valence of opinion, and content variables by 49% while the remaining 51% is explained by other variables that are not contained in the regression model.